Une « recommandation pour la conservation-restauration du patrimoine culturel » - Monica Martelli Castaldi; David Aguilella Cueco; Jeremy Hutchings; E.C.C.O. European Confederation of Conservator-Restorer’s Organisations (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
The draft of the first European Recommendation for the Conservation-Restoration of Cultural Heritage proposed by E.C.C.O., written with the support of ICCROM and participation of ENCoRE signifies a further step towards guaranteeing preservation of cultural heritage and greater recognition of the actors in this field. The Recommendation takes into consideration the need to define and regulate the field itself as a whole. This article presents this document and places it within the context of the work carried out by E.C.C.O. which includes other efforts to define the Conservation-Restoration profession, raise awareness and ensure the continued preservation of cultural heritage as a whole.